2022
DOI: 10.1177/19485506211070674
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Shyness from Late Childhood to Adolescence: A Longitudinal Study of Mexican-Origin Youth

Abstract: Shyness, the tendency to be inhibited and uncomfortable in novel social situations, is a consequential personality trait, especially during adolescence. The present study examined the development of shyness from late childhood (age 10) through adolescence (age 16) using data from a large, longitudinal study of Mexican-origin youth ( N = 674). Using both self- and mother-reports of shyness assessed via the Early Adolescent Temperament Questionnaire–Revised, we found moderate to high rank-order stabilities acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The selected measurement invariance model was retained in the next step where we compared the fit indices of three different LGC models: (a) no growth model, where only the level was estimated; (b) linear growth model, where the slope loadings were fixed to be 0, 2, 4, 6 at Ages 10, 12, 14, and 16; and (c) latent basis model, where the first and last time points of the slopes were fixed to 0 and 6, respectively, and the middle time points were freely estimated in order to detect nonlinearities in the growth model. We considered model fit, as well as parsimony, when selecting a LGC model for each domain and facet (for more details about model fitting and comparison, see Lawson et al, 2023, in press). For the broad and narrow NEM domains that were first examined in the present study, descriptive statistics and reliabilities by wave are shown in , results of longitudinal measurement invariance analyses are shown in , and model statistics for the LGC models are shown in .…”
Section: Methodsmentioning
confidence: 99%
“…The selected measurement invariance model was retained in the next step where we compared the fit indices of three different LGC models: (a) no growth model, where only the level was estimated; (b) linear growth model, where the slope loadings were fixed to be 0, 2, 4, 6 at Ages 10, 12, 14, and 16; and (c) latent basis model, where the first and last time points of the slopes were fixed to 0 and 6, respectively, and the middle time points were freely estimated in order to detect nonlinearities in the growth model. We considered model fit, as well as parsimony, when selecting a LGC model for each domain and facet (for more details about model fitting and comparison, see Lawson et al, 2023, in press). For the broad and narrow NEM domains that were first examined in the present study, descriptive statistics and reliabilities by wave are shown in , results of longitudinal measurement invariance analyses are shown in , and model statistics for the LGC models are shown in .…”
Section: Methodsmentioning
confidence: 99%